ANALYSIS OF HORIZONTAL FISCAL IMBALANCE IN SOUTH SULAWESI PROVINCE: WILLIAMSON INDEX AND KLASSEN TYPOLOGY APPROACH - Ahmad Romadhon (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
This study aims to investigate horizontal fiscal imbalance in South Sulawesi Province using the Williamson Index and Klassen Typology analysis approach. The province has abundant natural resources. However, it faces complex economic dynamics, leading to disparities in the distribution of economic benefits between regions. The results of the Williamson Index analysis show significant fluctuations in the level of fiscal imbalance over the 2018-2022 period, emphasizing the need for effective policy interventions. Meanwhile, the Klassen Typology illustrates the economic diversity of different regions in South Sulawesi, with Makassar City being a prominent center of economic growth. This research makes an important contribution to the understanding of fiscal imbalance at the regional level and provides a basis for more focused and data-driven policy formulation. Taking into account economic, social, and policy aspects, this study proposes a differentiated and inclusive policy approach to address fiscal imbalance, promote equitable economic growth, and achieve sustainable development in South Sulawesi.